Micro-PET imaging of [18F]fluoroacetate combined with [18F]FDG to differentiate chronic Mycobacterium tuberculosis infection from an acute bacterial infection in a mouse model: a preliminary study. Issue 6 (June 2019) - Tsao, Chin-Ho; Wu, Chun-Yi; Chang, Chi-Wei; Wang, Hsin-Ell; Shih, Bing-Fu; Liu, Ren-Shyan
Abstract : Background: Mycobacterium tuberculosis (TB) infection is one of the deadliest infectious diseases worldwide and is responsible for 1.7 million deaths per year. The increase in multidrug-resistant TB poses formidable challenges to the global control of tuberculosis. TB infection could easily yield false-positive results in fluorine-18-fluorodeoxyglucose ([ 18 F]FDG) PET imaging for cancer detection because of its high [ 18 F]FDG uptake. We describe the combined [ 18 F]FDG PET with fluorine-18-fluoroacetate ([ 18 F]FAC), a promising analog of carbon-11-acetate, for targeting glycolysis and de novo lipogenesis, respectively, to determine the metabolic differences between chronic TB infection and acute infection. Materials and methods: Six-month-old BALB/c mice were inoculated with Mycobacterium bovis to induce chronic TB infection, and Escherichia coli as well as Staphylococcus aureus to induce acute infection for an in-vivo imaging study. Eighteen days after inoculation for chronic TB infection and 5 days for acute infection, both [ 18 F]FDG and [ 18 F]FAC micro-PET were performed on the infected mice. Analysis of variance and the Tukey honest ad-hoc test were carried out to determine differences among treatment with different bacterial infections. Results: TB infection showed much lower [ 18 F] FAC accumulation than acute infection. However, both TB infection and acute infection exhibited high [ 18 F]FAC accumulation. Conclusion: The marked metabolic differences in de novo lipogenesis and glycolysis in [ 18 F]FDG and [ 18 F]FAC uptakes in micro-PET imaging, respectively, help to differentiate chronic TB infection from acute infection.